Macrobenthic community structure and distribution in the Gunung Berlumut recreational forest, Kluang, Johor, Malaysia. - Aweng Eh Rak; Ismid Said; Maketab Mohamed; Ahmad Abas (2010)
The macro invertebrate community structure was surveyed at Sungai Dengar sub-catchment which is located at Gunung Berlumut Recreational Forest in Kluang , Johor from 08 to 11 August 2009 by using surber net. Based on the results, it shows that Chironomidae were abundant at the pristine-pristine site which is the most up-stream (undisturbed) located on the Gunung Berlumut and also at the station B2 which is pristine station located at the toe of Gunung Berlumut but nevertheless the number of individual taxa are much higher at impact sites (C1 & C2). The highest Shannon- Wiener diversity Index was at the impact station (C2) which is located at the palm oil area and the lowers value located at the most cleaned site (A) which is located on the top of Gunung Belumut. Simpson Dominance Index and Margalef Richness Index was also highest at station C2 which is the impact sites and station A also recorded the lowest value. So, even though station C2 which was categorized as the impact station recorded the highest Shannon-Wiener Diversity Index and Margalef Richness Index but it also shows that some of the species dominated the area, which means the taxa distribution was not evenly distributed. The result also shows that both stations which was the cleanest (reference) and the impact did not fulfill Ephemeroptera, Plecoptera and Trichoptera (EPT) Index requirement which both stations did not have EPT taxa. Station B1 recorded the highest EPT index (9.4) and followed by station B2 (0.9) and the lowers was station C1 (0.4). Based on the above results, we can suggest that, macro invertebrate community structure does not depend solely on water quality of the river but it also depends on other factors such as habitat characteristics, river morphology, river riparian, canopy cover, etc., especially river substrate compositions.